2019
DOI: 10.1002/pri.1822
|View full text |Cite
|
Sign up to set email alerts
|

Physical therapy musculoskeletal imaging authority: A survey of the World Confederation for Physical Therapy Nations

Abstract: Objectives Medical evidence largely supports PTs in expanded roles, however, healthcare policy within the United States (USA) typically restricts PTs from ordering musculoskeletal (MSK) imaging. It is unknown how MSK imaging policy in the USA compares to other World Confederation for Physical Therapy (WCPT) member nations. The primary objective of our study was to investigate the authority of PTs to order MSK imaging. A secondary objective was to identify factors associated with the authority for PTs to order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Approximately 80% of the participants reported that they have musculoskeletal imaging referral rights. Mabry et al [ 6 ] examined physiotherapists’ MI authority in 81 countries (WCPT member nations); only one-third of the countries had affirmative policies. Among the countries were African nations such as Ethiopia and Zambia with full MI authority.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 80% of the participants reported that they have musculoskeletal imaging referral rights. Mabry et al [ 6 ] examined physiotherapists’ MI authority in 81 countries (WCPT member nations); only one-third of the countries had affirmative policies. Among the countries were African nations such as Ethiopia and Zambia with full MI authority.…”
Section: Discussionmentioning
confidence: 99%
“…Among the countries were African nations such as Ethiopia and Zambia with full MI authority. Others were Benin, Ghana, Swaziland, Malawi, South Africa, Rwanda, Tanzania, and Zimbabwe with partial authority covering mostly, the use of plain X-ray and MRI [ 6 ]. Although the majority of the participants reported having MI authority in their practice settings, the MRTB (Physiotherapy Practice) Act 2004 neither affirmed nor restricted Nigerian physiotherapists from MI referral [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research is needed to understand how experienced clinicians use MSK-US, which will bridge gaps related to the scope of practice and MSK-US specialized education needs. 16,32 The development of clinical reasoning skills is essential for physical therapy practice. Yet, limited information exists about the distinct knowledge, skills, and professional behaviors used in applying MSK-US for patient care and how to develop these skills in students and practicing PTs.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Traditional pathways can comparably delay care by one year [1]. Many physical therapists within the United States of America are restricted from referring patients directly to a radiologist by their respective state practice acts or state physical therapy board rules [2]. However, when physical therapists are authorized to refer for imaging, they do so appropriately [3,4], accurately [5], and without harm to patients [6].…”
mentioning
confidence: 99%